Effect of traditional therapeutics on prevalence and clinical outcomes of coronavirus disease 2019 in Chinese patients with autoimmune diseases - Saisai Huang; Xiaolei Ma; Juan Cao; Mengru Du; Zhiling Zhao; Dandan Wang; Xue Xu; Jun Liang; Lingyun Sun (Journal of Translational Autoimmunity, 2024)
The impact of the Coronavirus disease 2019 (COVID-19) pandemic on autoimmune diseases (AID) patients has been an important focus. This study was undertaken to characterize the incidence, clinical manifestations and hospitalization among AID affected by COVID-19 and to analyze the association between immunomodulatory medication and these outcomes. Clinical, demographic, maintenance treatment, symptoms and disease course data and outcomes of AID patients with COVID-19 infection were assessed via an online survey tool and printed copy from 1 January till February 28, 2023. A total of 432 patients with AID were enrolled in the study. The results showed the most common conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) was hydroxychloroquine (HCQ). The usage of csDMARDs didn't increase the risk of COVID-19 infection. Patients who warranted hospitalization were significantly older. ILD was associated with higher hospitalization rate. No csDMARDs other than calcineurin inhibitor (CNI) was associated with increased risk of hospitalization. HCQ intake was associated with cough. Compared with no glucocorticoids (GCs) group, high doses of GCs were accompanied with higher proportion of gastrointestinal symptoms and tachycardia, lower proportion of sore throat and ageusia. GCs didn't provoke the COVID‐19 infection in patients with AID, but chronic use of oral GCs was significantly more common in those requiring hospitalization, and higher dose of GCs were correlated with higher risk of hospitalization. 97 patients discontinued csDMARDs after infection, which resulted in an elevated risk of hospitalization. Meanwhile, withdrawal of csDMARDs was associated with higher odds of disease flare and lower proportion of remission than maintenance groups. Collectively, our analysis provides the evidence that maintenance treatment of csDMARDs may be more prudent for AID patients during COVID-19 pandemic.